2013
DOI: 10.1117/1.oe.52.5.056601
|View full text |Cite
|
Sign up to set email alerts
|

Tip-tilt restoration of a segmented optical mirror using a geometric sensor

Abstract: Abstract. We present a geometric sensor to restore the local tip-tilt in a segmented surface using the Van Dam and Lane algorithm [M. A. van Dam and R. G. Lane, Appl. Opt. 41(26), 5497-5502 (2002)]. The paper also presents an implementation of this algorithm using graphical processing units as specialized hardware. This compute unified device architecture implementation achieves real-time results inside the stability time of the atmosphere for resolutions of up to 1024 × 1024 pixels. © The Authors.Published b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The method proposed in [9] estimates a wave front phase from two symmetrically defocused images. In this method, the phase resolution is only limited by the sensor resolution, besides it has been demonstrated that real-time implementations of the method are possible [10].…”
Section: Relation Of Light Field and Focal Stackmentioning
confidence: 98%
“…The method proposed in [9] estimates a wave front phase from two symmetrically defocused images. In this method, the phase resolution is only limited by the sensor resolution, besides it has been demonstrated that real-time implementations of the method are possible [10].…”
Section: Relation Of Light Field and Focal Stackmentioning
confidence: 98%
“…The experimental setup is identical to that of the nlCWFS but simpler, as it considers only intensity measurements at two planes symmetrically placed at both sides of the aperture. Geometrical optics propagation of the photons is considered, so that the technique is applicable to extended and polychromatic sources [10].…”
Section: Aolimentioning
confidence: 99%
“…In the ELTs, the number of microlenses and edges grows enormously and, the difficulty of precise alignment requires the search for simpler solutions. The geometric sensor corresponds to a much simpler optical design; in one hand it has been recently demonstrated that it is capable of measuring tip-tilt in every segment with high sensitivity (Fernández-Valdivia et al [2]), and in the other hand it is well known that the geometric sensor is sensitive to the local piston between segments (Rodríguez-Ramos et al [3]). Then co-phasing of the surface can be carried out using only the geometric sensor.…”
Section: Introductionmentioning
confidence: 98%